The influence of non linear editing in documentary video production - Teresa, anak Billy Bayang (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this study was to identify the influence of the development in technology on the production of documentary films, especially on the aspect of post-production editing. The main reason the researcher wanted to study the subject in greater depth, through a self-conducted experiment, was the influence of technology on the workflow process in post-production of films. The researcher studied the theories and collected data from the content analysis, carried out from a review of the literature